The economics of regional integration - Nagy, Sándor Gyula, 1980- (Routledge advances in regional economics, science and policy., 2025)
"This book develops a new methodological framework for measuring the efficiency of regional integration and the integration profile of member states. It includes rich case studies, which offer a comparative analysis of ten integrations spanning four continents - The Americas, The European Union, Africa and Asia. The book shows the importance of regional (economic) integration in the world economy, based partially on descriptive analyses and partially on the authors' new methodological framework, based on a new composite index of integration profile. It implements and quantifies relevant theories (e.g. integration maturity, competitiveness, economic development, convergence) to one framework and a composite indicator. This helps to arrive at a more precise measurement of these integrations, resulting in useful feedback for decision makers and leading to policy-recommendations for each organization to improve efficiency or to include new members. It presents a comparative perspective of regional integration, based on case studies, by applying the same theoretical framework and a comprehensive methodology for assessing the economic readiness of membership seeking countries but also considering regional differences. It investigates the impact of regional integration on income inequality and poverty reduction, by examining how common development, economic policies and social programs implemented by regional organizations affect the distribution of income and wealth among member states. The comprehensive investigation of regional integration, covering economic, social, and institutional factors makes the book highly relevant for advanced students, researchers, and scholars. Additionally, its potential policy context application makes it useful for policymakers and practitioners participating in regional integration programs"--